Factors influencing roll-out of an m-Health intervention in India: Results from a dynamic and responsive process evaluation - Avula, Rasmi; Menon, Purnima; Bajaj, Sumati; Mani, Sneha; George, Nitya (American Society for Nutrition, 2020)
Implementation research can support iterative program improvement, yet limited examples of such dynamic experiences exist. We conducted a multi-stage and multi-method process evaluation (PE) of a large-scale m-Health intervention in India that currently reaches 581,282 frontline workers (FLWs). The intervention (Common Application Software (CAS)) includes a smartphone application that digitizes FLW service-tracking registers and acts as a job aid and multiple dashboards for real-time monitoring. We examined factors affecting the roll-out of CAS in two Indian states.